Teknik Modulasi Untuk Inverter Multilevel Cascaded H-Bridge (CHB) Satu Fasa Menggunakan Arduino Mega 2560 - Ida Bagus Fery Citarsa; I Nyoman Wahyu Satiawan Wahyu Satiawan (DIELEKTRIKA, 2019)
Single-phase multilevel Cascaded H-bridge inverter composed of several inverter cells. A DC voltage combination system is connected to each input voltage on each inverter cell to form a multilevel voltage output waveform. The inverter uses an electronic switch to form each voltage from the input DC voltage. The programming system is generated using Arduino Mega 2560 so that switch state can be set at a certain time so that the output voltage waveform in the inverter can be arranged. In this research, an investigation of the best switching technique was performed on a two-cell Cascaded H-bridge inverter with different input DC voltage ratios. The result shows that the THDv value is 14.8% for 1: 1 DC voltage ratio, 9.9% for 1 : 2 DC voltage ratio and 9.6% for 1: 3 DC voltage ratio.